Host defense function of the airway epithelium in health and disease: clinical background - Message, Simon D. (J Leukoc Biol, 2003)
Respiratory infection is extremely common and a major cause of morbidity and mortality worldwide. The airway epithelium has an important role in host defense against infection and this is illustrated in this review by considering infection by respiratory viruses. In patients with asthma or chronic obstructive pulmonary disease, respiratory viruses are a common trigger of exacerbations. Rhinoviruses (RV) are the most common virus type detected. Knowledge of the immunopathogenesis of such RV‐induced exacerbations remains limited, but information is available from in vitro and from in vivo studies, especially of experimental infection in human volunteers. RV infects and replicates within epithelial cells (EC) of the lower respiratory tract. EC are an important component of the innate‐immune response to RV infection. The interaction between virus and the intracellular signaling pathways of the host cell results in activation of potentially antiviral mechanisms, including type 1 interferons and nitric oxide, and in the producton of cytokines and chemokines [interleukin (IL)‐1β, IL‐6, IL‐8, IL‐11, IL‐16, tumor necrosis factor α, granulocyte macrophage‐colony stimulating factor, growth‐regulated oncogene‐α, epithelial neutrophil‐activating protein‐78, regulated on activation, normal T expressed and secreted, eotaxin 1/2, macrophage‐inflammatory protein‐1α], which influence the subsequent induced innate‐ and specific‐immune response. Although this is beneficial in facilitating clearance of virus from the respiratory tract, the generation of proinflammatory mediators and the recruitment of inflammatory cells result in a degree of immunopathology and may amplify pre‐existing airway inflammation. Further research will be necessary to determine whether modification of EC responses to respiratory virus infection will be of therapeutic benefit.